Avaliação de impacto de políticas de segurança: o caso das Unidades de Polícia Pacificadora (UPPs) no Rio de Janeiro - Butelli, Pedro Henrique (2015)
This thesis aims on the impact evaluation of the Pacifying Police Units policy, incorporating the causality relations through differences-in-differences regressions with multiple specifications in order to measure the impacts on crime, schooling, income, inequality, possession of assets and immigration.